Potentials Of Leading Sectors In Bangka Belitung Island Province On 2013-2017 - Atik Yulianti (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
Decentralization and regional autonomy policies provide opportunities for development of governments and communities in the regions. The economic and financial potential needs to be extracted and processed, so it could be a tangible output that gives an additional value to the product which lead to improving the welfare of the people in the Bangka Belitung Islands Province. Regional economics can be divided into two sectors, namely basic activities and activities rather than bases. This study uses Location Quotient method to find out and analyze the basic or superior sectors in the Bangka Belitung Islands Province. Based on the results of the research, Mining and Excavation sector, Government administration sector, Agricultural sector, Health and services sector, Real estate sector, Manufacturing industry and the big and retail trade sector; are those who have more than 1 local offering so they can be favored for the Bangka Belitung Islands Province in 2013-2017.